Efficacy and tolerability of repetitive transcranial magnetic stimulation over dorsolateral prefrontal cortex for episodic migraine prophylaxis - Mohamad Safiai, Nabil Izzaatie (2022)
Migraine is a disabling primary headache disorder that imposes a substantial burden on the sufferers and society. The role of non-pharmacological therapy such as neuromodulators is increasingly being recognised as a potential therapy for migraine. Repetitive transcranial magnetic stimulation (rTMS) is one of the neuromodulators used in many studies. However, its efficacy in the context of migraine prevention remains unknown, especially in the application on the dorsolateral prefrontal cortex (DLPFC). Our meta-analysis showed a significant reduction in acute medication intake (Mean Difference = 9.78, p =.02, 95%CI = 1.60, 17.96, p =.02) and functional disability (Mean Difference = 8.00, p <.05, 95%CI = 4.21, 11.79). In this clinical trial, subjects were randomised into rTMS and sham groups. Both groups received five treatment sessions within two weeks and were followed up for three months. Quality of life among the subjects was examined using MIDAS, MSQ v2.1 and EQ-5D questionnaires at baseline and month 3. Physiological changes in transcranial blood flow and serotonin levels were also explored. Results showed that rTMS over DLPFC was safe with a discontinuation rate of 15.8%. However, the mean number of migraine days, migraine frequency and pain intensity between the two groups did not significantly differ. For the quality of life, the differences in MSQ v2 .1, EQ-5D and MIDAS components were also not significant. Similarly, there were no significant differences observed between the two groups for serotonin concentration and Doppler findings. In conclusion, this study found that both rTMS and sham similarly reduced mean migraine days with good tolerability. However, the differences in terms of clinical, biochemical, and neurophysiological markers were statistically insignificant. Current evidence is still not sufficient to recommend the use of rTMS over DLPFC to prevent episodic migraine. Future research should explore different clinical profiles and stimulation protocols.